Apoplastic interactions between plants and plant root intruders - Mitsumasu, Kanako; Seto, Yoshiya; Yoshida, Satoko (Frontiers in Plant Science, 2015)
Numerous pathogenic or parasitic organisms attack plant roots to obtain nutrients, and the apoplast including the plant cell wall is where the plant cell meets such organisms. Root-parasitic angiosperms and nematodes are two distinct types of plant root parasites but share some common features in their strategies for breaking into plant roots. Striga and Orobanche are obligate root parasitic angiosperms that cause devastating agricultural problems worldwide. Parasitic plants form an invasion organ called a haustorium, where plant cell wall degrading enzymes (PCWDEs) are highly expressed. Plant-parasitic nematodes are another type of agriculturally important plant root parasite. These nematodes breach the plant cell walls by protruding a sclerotized stylet from which PCWDEs are secreted. Responding to such parasitic invasion, host plants activate their own defense responses against parasites. Endoparasitic nematodes secrete apoplastic effectors to modulate host immune responses and to facilitate the formation of a feeding site. Apoplastic communication between hosts and parasitic plants also contributes to their interaction. Parasitic plant germination stimulants, strigolactones (SLs), are recently identified apoplastic signals that are transmitted over long distances from biosynthetic sites to functioning sites. Here, we discuss recent advances in understanding the importance of apoplastic signals and cell walls for plant-parasite interactions.